Variation in Amino Acid Content Among Three Aloe Species - Kyoung Kim, Yong; Yeon Suh, Seung; Romij Uddin, Md.; Bok Kim, Yeon; Hoon Kim, Haeng; Won Lee, Sang; Un Park, Sang (Asian Journal of Chemistry, 2013)
Aloe species are well known as medicinal plants and are also used in various commercial products. Here, we have analyzed the amino acid contents of three Aloe species (Aloe arborescens, A. vera and A. saponaria) and have discussed the differences in amino acid levels among these three species. A total of 24 and 23 amino acids were detected in A. vera and A. saponaria, respectively, whereas only 17 amino acids were detected in A. arborescens. A. vera had high levels of ammonia, aspartic acid, glutamic acid, serine, arginine, valine, alanine, whereas A. saponaria contained the highest levels of ammonia, glutamic acid, aspartic acid, valine and alanine. In particular A. vera contained 11 times more g-amino butyric acid than A. arborescens did. A. vera contained a greater overall concentration of amino acids than the other species did. The mean concentrations of phosphoserine and taurine were higher in A. arborescens than in the other Aloe species. In conclusion, among these Aloe species, A. vera had the highest total amino acid concentration and the greatest variation in amino acid contents.